2016
DOI: 10.1111/1758-2229.12373
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of fungal assemblages across different marine habitats

Abstract: Fungi are a highly diverse group of microbes that fundamentally influence the biogeochemistry of the biosphere, but we currently know little about the diversity and distribution of fungi in aquatic habitats. Here we describe shifts in marine fungal community composition across different marine habitats, using targeted pyrosequencing of the fungal Internal Transcribed Spacer (ITS) region. Our results demonstrate strong partitioning of fungal community composition between estuarine, coastal and oceanic samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 21 publications
8
41
2
Order By: Relevance
“…The fungal results, especially taxonomic classifications, presented here should be considered cautiously due to a number of issues that have recently received attention regarding the use of next-generation sequencing for ecological studies of fungi, including incomplete taxonomic databases and lack of a control mock community, sequencing target, and alignment and clustering methods (35, 36). Nevertheless, OTU-based analyses tended to agree well with those from prokaryotic community characterization (discussed below), suggesting that unclassified sequences may simply represent unexplored marine fungal diversity (32). Further analyses must await new sequencing technologies, bioinformatics approaches, and further development of taxonomic databases.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The fungal results, especially taxonomic classifications, presented here should be considered cautiously due to a number of issues that have recently received attention regarding the use of next-generation sequencing for ecological studies of fungi, including incomplete taxonomic databases and lack of a control mock community, sequencing target, and alignment and clustering methods (35, 36). Nevertheless, OTU-based analyses tended to agree well with those from prokaryotic community characterization (discussed below), suggesting that unclassified sequences may simply represent unexplored marine fungal diversity (32). Further analyses must await new sequencing technologies, bioinformatics approaches, and further development of taxonomic databases.…”
Section: Discussionmentioning
confidence: 96%
“…Fungal communities in open ocean environments are only beginning to receive the same attention as prokaryotes and remain largely uncharacterized (32). While the majority of fungal community sequences were unclassified in this study, a previous report found members of class Sordariomycetes to be abundant in Porites astreoides near Panama (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad distribution of these shared OTUs contributed to the homogenization of fungal communities across the western Arctic, determined through NMDS ordination. Fungal community structure in the western Arctic Ocean was neither strongly partitioned, nor substantially spatially heterogeneous, as reported in other systems (Jeffries et al ., ). We hypothesize that this homogenization in the Arctic Ocean is a result of the strong oceanographic processes that advect water and sea ice eastward from the Bering Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to determine the spatial distribution of fungi through the western Arctic and sub‐Arctic region by using HTS to target the frequently used 18S rRNA gene, supplemented by deep sequencing of the 28S rRNA gene. We hypothesized that geographic distance and site‐specific hydrography would partition marine fungi into distinct communities, as previously reported (Jeffries et al ., ). To understand the phylogenetic diversity of marine chytrids, we generated 28S rRNA gene clones from select geographical regions with detectable chytrids.…”
Section: Introductionmentioning
confidence: 99%